A juventude remanescente de Quilombo da Comunidade Bastiões (CE): tensões e identidade - Silva, Sâmia Paula dos Santos (2016)
This research discuss the topic of youth in a community remaining quilombos. It aims to investigate how it is and says the quilombo identity of the young residents of the bastions community in the state of Ceara (CE), to know the daily lives of youth in the Bastions community in particular to forms of cultural expressions. understand how cultural expression groups influence the formation of youth in the community. To meet them, we adopted as methodological procedures free observation and semi-structured interviews to investigate how to organize groups and develop their cultural activities. During the research we have the participation of ten subjects. The results show that the community social values were built by the ancestors and survive today. The new generations are expressed in the community through daily or in large events activities. The town has social problems that have hit many generations, such as the difficulty of access to information and knowledge. This situation affects mainly young people who have their training hampered by failures in the social structure. With the advent of the internet, young people began to develop cultural and educational activities that contribute to the development of local customs and improves the quality of education in regard to broad access to information and knowledge among these activities are the creation of educational blogs, theater and dance groups.